Buckling strain effects on electronic and optical aspects of penta-graphene nanostructure. (September 2019) - Alborznia, Hamidreza; Naseri, Mosayeb; Fatahi, Negin
Abstract: Using the first principles calculations based on density functional theory (DFT), the effects of vertical compressive strain on the electronic and optical properties of the recently proposed 2D carbon allotrop namely penta-graphene are investigated. With the aim of validating our results, initially, the structural and the electronic properties of the pristine penta-graphene were regained. Our results display well-matched properties with the related works found in the literature. Our investigation into the electronic properties of the penta-graphene demonstrates that under vertical compressive strain conditions, an indirect to direct band gap transition occurs. Likewise, we also investigated its optical properties under strain conditions, showing that its optical behaviors match with its electronic ones. Consequently, the obtained results suggest 2D penta-graphene as a suitable material for designing electro-optic devices. Highlights: The electronic and optical properties of penta-graphene under buckling effects are investigated. Under buckling effects, an indirect to direct band gap transition occurs. The electronic and optical properties of the penta-graphene can be effectively tuned by buckling effects. The obtained results suggest 2D penta-graphene as a suitable material for designing electro-optic devices.